KEARIFAN LOKAL DALAM ARSITEKTUR VERNAKULAR RUMOH ACEH - Nova Purnama Lisa (Jurnal MEDIAN Arsitektur dan Planologi, 2012)
Vernacular Architecture is an area of architectural theory that studies the structures made by empirical builders without the intervention of professional architects. There exist many areas of non-professional architectural practice, from primitive shelter in distant communities to urban adaptations of building types that are imported from one country to another. Because of that, vernacular architecture is a very open, comprehensive concept. It is in fact used as a shortcut and a synonymous for several different practices, and theoretical stands on those practices. There is a unique technology in the house of Aceh (Indonesia : Rumoh Aceh) to save homes from fire danger. As we know, the biggest risk in the traditional tropical houses made almost entirely of buildings from nature such as wood, bamboo, thatch, leaves. All are highly flammable. The Traditional Aceh house has a fairly basic designs consisting of a rectangular platform resting on piles with a longitudinal gabled roof. Aceh houses are usually divided into three with the central area reserved for sleeping. The entrance is usually in the middle of one of the long sides and gable end are often decorated with geometric or other non representational design. Aceh Houses is Islamic building design.